Bandgap Engineering in Wurtzite GaAs Nanowires by Hydrostatic Pressure - 杨爽 丁琨 窦秀明 喻颖 倪海桥 牛智川 江德生 孙宝权 (Chinese physics letters, 2015)
Band structure of wurtzite （WZ） GaAs nanowires （NWs） is investigated by using photoluminescenee measurements under hydrostatic pressure at 6 K. We demonstrate that WZ GaAs NWs have a direct bandgap transition with an emission energy of 1.53eV, corresponding to the optical transition between conduction band Г7c and valence band Г9v in WZ GaAs. The direct-to-pseudodirect bandgap transition can be observed by applying a pressure approximately above 2.5 GPa.